An Analysis Of Derivational Affixes In The Rainbow Troops Novel By Andrea Hirata - Umar, Umar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2026)
Morphological analysis is the main areas in studying vocabulary. Morphological analysis itself is analysis that is breaking a word into its elements (root, prefix and suffix). Meanwhile, derivational affixes is the part of morphological analysis. So, it is important for the students to study about derivational affixes. When the students are able to identify derivational affix, they can develop their vocabulary because from just one word it can gain many words with different part of speech. Novel is a long essay in prose and contains a series of human life stories with others around them with accentuate the character and nature of the actor. The Rainbow Troops Novel By Andrea Hirata is a novel inspired by a true story from the author, that is Andrea Hirata Having seeing such phenomenon, the writer found that mastering English is not easy if the students are lack of vocabulary. This research aimed to find out the derivational affixes in The Rainbow Troops Novel By Andrea Hirata. This research is descriptive qualitative research where researcher tries to find out the derivational affix and the roots from the words in The Rainbow Troops Novel By Andrea Hirata without using statistical calculation. In this research the writer uses all of words that are attached prefix and suffix as the data. The data source is all the chapters which are the beginning of the story, rising the case and the solution in The Rainbow Troops Novel By Andrea Hirata. The result of analyzing data were gained the derivational affixes that found in The Rainbow Troops Novel By Andrea Hirata are in- (1), un- (22), as prefixes, while the suffixes are –ly (125), -able (10), -er (2), -al (10), -ous (7), -ess (2), -ion (12), -ship (3), -ment (22), -ful (17), - ary (4), -less (14), -ity (6), - ness (12). In he Rainbow Troops Novel By Andrea Hirata, the roots from the words that has been classified based on the part of speech are 96 (adjective), 81 (noun), 86(verb), 2 (adverb). From the conclusion of this research, the writer suggests that to improve their mastery of vocabulary, the readers should be apply the derivational affixes by breaking the word into its elements root and affixes because from one word they can get the structure of words and they also find how the words built. By knowing the roots, the readers can build the word by themselves.